Studi Literatur: Efektifitas Senam Yoga Terhadap Nyeri Punggung Ibu Hamil Trimester III - Rita Ade Swastika; Ida Prijatni; Dian Aby Restanty (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2021)
Back pain is one of the discomforts of pregnant women in the form of pain that occurs in the lumbosacral area. One way to reduce discomfort is exercise during pregnancy, one of which is yoga. Yoga in pregnancy describes specific postures and techniques that are beneficial to expectant mothers and help relieve discomfort caused by bodily changes during pregnancy. The purpose of this study was to determine the effectiveness of yoga exercise on back pain for pregnant women with TM III. This literature study was obtained from searching scientific research articles from the 2010-2020 range using Google Schoolar. The results of the literature study obtained 244 articles, which after the identification, screening, and eligibility process from 244 articles there were 9 articles that matched the researcher's inclusion criteria. From these 9 journals, it can be concluded that yoga exercise is effective in reducing back pain for pregnant women with TM III. Yoga exercise can produce endorphins that trigger feelings of comfort, pleasure, and happiness produced by the central nervous system and pituitary gland, endorphins function to relieve pain because these hormones can block opioid receptors which can block pain-conducting signals. Keywords: yoga exercise, back pain, pregnant women